Method for researching influence of intermediate layer on assembly and performance of bimetallic interface

Microtextured FeCoNiCr-M high-entropy alloy coating was prepared by electrochemical deposition and femtosecond laser technology, and liquid-solid forming was performed as an intermediate layer, which solved the problem of insufficient interface bonding strength of Al/Fe bimetallic and significantly improved the interface bonding strength and performance of composite materials.

CN119804307APending Publication Date: 2025-04-11恒利智造(云南)科技有限公司 +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411898379.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The insufficient bonding strength of Al/Fe bimetallic interface seriously restricts its application in engine special-shaped structural parts.

Method used

The microtextured FeCoNiCr-M high-entropy alloy coating was prepared as an intermediate layer by electrochemical deposition and femtosecond laser technology, and the interface structure and performance of Al/HEA/Fe composite materials were optimized through liquid-solid forming technology.

Benefits of technology

The Al/Fe bimetal interface bonding strength is significantly improved, the interface structure and performance of composite materials are optimized, and its application in engine special-shaped structural parts is promoted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804307A_ABST
    Figure CN119804307A_ABST
Patent Text Reader

Abstract

The invention relates to the field of bimetal composite materials, in particular to a method for researching the influence of an intermediate layer on bimetal interface assembly and performance, which comprises the following steps: electrochemically depositing a FeCoNiCr-M high-entropy alloy coating; a micro-textured high-entropy alloy coating is constructed in a laser controllable manner; according to Al / HEA / Fe composite material liquid-solid forming process optimization and structure property characterization, the Al / HEA / Fe composite material liquid-solid forming process optimization and structure property characterization method has the following beneficial effects that according to the requirement for Al / Fe bimetal high interface bonding strength, the microtextured high-entropy alloy coating is prepared through the electrochemical and femtosecond laser composite technology, the microtextured high-entropy alloy coating serves as a middle layer between a solid steel matrix and a liquid aluminum alloy melt, and the high-strength Al / HEA / Fe composite material is obtained; the Al / HEA / Fe composite material is obtained through a liquid-solid forming technology, and the Al / HEA / Fe composite material is obtained through high-entropy alloy component / content optimization, coating surface structure design, technological parameter regulation and control and the like on the basis of thermal and dynamic calculation and experimental data analysis. And research on the aspects of a high-entropy alloy coating solid solution phase forming mechanism, a composite material interface structure evolution rule, an interface strengthening mechanism and the like is carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention is a research method for the influence of an intermediate layer on the assembly and performance of a bimetallic interface, and belongs to the field of bimetallic composite materials. Background Art

[0002] In the automotive industry, energy consumption, fuel efficiency and environmental issues have become the focus of attention. As the "heart" of the car, the lightweight and reliability of the engine are of great practical significance for ensuring the power, economy and environmental protection of the car. The aluminum / iron bimetallic composite material (hereinafter referred to as "Al / Fe bimetallic") prepared by liquid-solid forming technology combines the advantages of aluminum's light weight, high thermal conductivity, high toughness, corrosion resistance and iron's high strength, high wear resistance and strong shock absorption, becoming an excellent material for the current engine lightweight design. However, facing the harsh working conditions of high temperature, high pressure and high load of the engine, the problem of insufficient interface bonding strength of Al / Fe bimetallic is particularly prominent, which seriously restricts its application in special-shaped structural parts of the engine. The design and controllable construction of the intermediate layer composition are the key development directions of Al / Fe bimetallic in the future. How to carry out basic research on the regulation of the interface of the Al / Fe bimetallic intermediate layer is of great practical significance for promoting the application of Al / Fe bimetallic in special-shaped structural parts of automobile engines. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a research method for the influence of the intermediate layer on the assembly and performance of the bimetallic interface, so as to solve the problems raised in the above background technology.

[0004] In order to achieve the above object, the present invention is implemented by the following technical solution: A method for studying the influence of an intermediate layer on the assembly and performance of a bimetallic interface comprises the following steps:

[0005] Step 1: Electrochemical deposition of FeCoNiCr-M high entropy alloy coating;

[0006] Based on the redox characteristics of electrochemical technology and the first principles, Cu, Mn and Zn, which are close to the standard electrode potential of the four elements FeCoNiCr, are selected as the fifth principal element. With the help of the CASTEP module in the MaterialsStudio software, through geometric optimization simulation, the lattice parameters, mechanical properties, thermodynamic parameters and physical properties of different FeCoNiCr-M high entropy alloys are clarified, the M component is optimized, and the influence of the salt solution concentration ratio of the five principal cations, the solution pH value and the type of additive solution parameters on the solid solution phase composition, element distribution, coating thickness and deposition rate of the high entropy alloy coating is systematically studied. Then, the single-factor experimental method is used to adjust the electrochemical process parameters of current density, solution temperature, deposition time and plating solution stirring frequency to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy.

[0007] XRD, SEM, TEM and EDS were used to characterize the phase structure and microstructure of the high entropy alloy coating, and thermodynamic calculations were used to clarify the solid solution phase formation mechanism of the high entropy alloy coating. Nanoindenter was used to detect the nanohardness and elastic modulus of the coating, and a scratch tester was used to obtain the bonding strength between the high entropy alloy coating and the steel substrate. Combined with the analysis of microstructure and basic mechanical properties, the influence of solution parameters and electrochemical process parameters on the performance of the high entropy alloy coating were explored, revealing the corresponding relationship between the type / content of the main element, process parameters and the organizational properties of the high entropy alloy coating.

[0008] Step 2: Laser controllable construction of micro-textured high-entropy alloy coating;

[0009] Optimize the texture pattern configuration that is conducive to improving the interface bonding strength, use femtosecond laser technology to construct micro-texture on the surface of high-entropy alloy coatings with excellent comprehensive performance, and study the influence of pattern parameters and laser process parameters on the phase structure and basic properties of high-entropy alloy coatings by adjusting texture pattern parameters and laser process parameters. Explore the filling law and spreading behavior of aluminum melt droplets on different texture surfaces, and provide suitable texture morphology for subsequent liquid-solid forming technology;

[0010] The three-dimensional morphology and two-dimensional profile curve of the texture pattern are obtained by laser 3D microscope to understand the variation law of the surface roughness of the micro-textured high-entropy alloy coating; SEM, XRD, EDS, and XPS are used to detect the micro-morphology, element valence state, and stress state of the micro-textured high-entropy alloy to reveal the burning behavior of the surface elements of the micro-textured high-entropy alloy and the stress distribution characteristics of the texture boundary; the influence of texture parameters on the high-temperature wetting performance of the aluminum alloy molten droplets used in Al / Fe bimetallic materials is clarified through solder wettability tests, and the laser process parameters are optimized in combination with SEM analysis feedback;

[0011] Step 3: Liquid-solid forming process optimization and microstructure and performance characterization of Al / HEA / Fe composites;

[0012] Based on the aforementioned process optimization parameters, a micro-textured high-entropy alloy coating was constructed on the surface of the steel substrate, and the whole was used as an embedded casting for liquid-solid forming research to explore the antioxidant ability of the micro-textured high-entropy alloy coating under different preheating conditions such as substrate surface state, preheating temperature, and preheating time; then the influence of different casting conditions such as aluminum liquid casting temperature, casting insulation time, and mold type on the composite interface reaction phase composition, element distribution state, reaction layer width change, and defect form was studied, and combined with kinetic analysis, the interface bonding characteristics and interface organization evolution of Al / HEA / Fe composites were revealed, and the reasons for the inhibition of aluminum-iron hard and brittle phases at the composite interface were clarified;

[0013] The phase composition / structure, element distribution, organizational morphology, grain size and orientation distribution interface characteristics of the interface reaction layer of the Al / HEA / Fe composite material were analyzed by SEM, EPMA, TEM, EDS and EBSD. The surface residual stress of the composite material was measured by X-ray diffraction, the residual stress at the interface was detected by nanoindentation, and the hardness distribution of the composite material along the interface was analyzed by nanoindenter. The interface bonding strength of the composite material before and after the addition of the high entropy alloy intermediate layer and before and after laser processing was tested and compared by a universal testing machine. Combined with the fracture morphology analysis, the interface strengthening mechanism of the micro-textured high entropy alloy intermediate layer assisted liquid-solid forming of Al / Fe bimetal was elucidated.

[0014] Specifically, the electrochemical deposition mechanism of the FeCoNiCr-M series five-element high entropy alloy coating: Taking the four-element FeCoNiCr high entropy alloy as the basic research system, the electrochemical deposition mechanism of the FeCoNiCr-M high entropy alloy coating is studied by adding alloying elements, adjusting the content of the main element and controlling the process parameters:

[0015] Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of FeCoNiCr-M high entropy alloys are simulated and predicted, and the types of M principal elements in the FeCoNiCr-M system are optimized to provide theoretical guidance for the principal element design of electrochemically deposited FeCoNiCr-M high entropy alloy coatings.

[0016] The influence of solution parameters and electrochemical process parameters on the microstructure and properties of high-entropy alloy coatings is systematically investigated. Combined with thermodynamic calculations, the electrochemical deposition mechanism of the solid solution phase in the high-entropy alloy coating is clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties is established.

[0017] Specifically, the laser-controllable construction mechanism of micro-texture on the surface of high-entropy alloy coatings:

[0018] Taking steel parts deposited with high-entropy alloy coatings with good comprehensive performance as processing objects, femtosecond laser technology is used to carry out the design of surface micro-texturing of high-entropy alloy coatings and the research on the mechanism of laser-controlled construction;

[0019] Systematically investigate the influence of laser process parameters on the microstructure and properties of high entropy alloy coatings, clarify the transformation behavior of the surface phase structure of high entropy alloys after laser irradiation; analyze the stress distribution characteristics, element burning behavior, and defect types of the surface of high entropy alloys, and reveal the laser action mechanism of the surface of high entropy alloy coatings;

[0020] Combined with high-temperature wetting performance tests, the filling state and spreading behavior of molten aluminum on the surface of micro-textured high-entropy alloy coatings are investigated, the influence of texture pattern parameters on the wetting performance of molten aluminum droplets is explored, and feedback is used to optimize the texture pattern parameters and laser process parameters.

[0021] Specifically, the interface microstructure evolution and strengthening mechanism of liquid-solid formed Al / HEA / Fe composites:

[0022] Steel parts with micro-textured high entropy alloy coatings were used as embedded castings, and Al / HEA / Fe composites were prepared by liquid-solid forming technology. The evolution law of the interface structure and the strengthening mechanism of the composites were studied by optimizing the liquid-solid forming process.

[0023] Study the effects of liquid-solid forming process parameters on the element diffusion behavior / distribution characteristics, dissolution rate and reaction phase composition of high entropy alloy coatings, and clarify the interface bonding characteristics and organizational structure evolution of composite materials after the introduction of micro-textured high entropy alloy intermediate layers;

[0024] Through the microscopic characterization and bonding strength test of the composite material interface, assisted by kinetic calculations, the composition / width changes, phase structure transformation and microtexture dissolution behavior of the composite material interface reaction layer are analyzed, revealing the interface regulation principle and interface strengthening mechanism of composite materials containing microtextured high entropy alloy intermediate layers.

[0025] Beneficial effects of the present invention:

[0026] In response to the demand for high interface bonding strength of Al / Fe bimetallic, it is planned to use electrochemical and femtosecond laser composite technology to prepare micro-textured high-entropy alloy coating, which will be used as an intermediate layer between the solid steel substrate and the liquid aluminum alloy melt, and the "Al / HEA / Fe composite material" will be obtained through liquid-solid forming technology. Based on thermal and kinetic calculations and experimental data analysis, through the optimization of high-entropy alloy component / content, coating surface structure design and process parameter regulation, research on the solid solution phase formation mechanism of high-entropy alloy coating, the evolution law of composite material interface organization and interface strengthening mechanism will be carried out.

[0027] Based on the cross-integration of multidisciplinary knowledge such as materials science, physical chemistry and computational materials science, an Al / HEA / Fe composite material with high interface bonding strength was developed by combining theoretical calculation with experimental analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0029] Figure 1 A technical roadmap for the research method of the effect of the intermediate layer on the assembly and performance of the bimetallic interface of the present invention;

[0030] Figure 2 Schematic diagram of electrochemical deposition of high entropy alloy coating;

[0031] Figure 3 Schematic diagram of the construction of micro-textured high entropy alloy coating;

[0032] Figure 4 Schematic diagram of liquid-solid forming of Al / HEA / Fe composites; DETAILED DESCRIPTION

[0033] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific implementation methods.

[0034] See also Figure 1-Figure 4 The present invention provides a technical solution: A method for studying the influence of an intermediate layer on the assembly and performance of a bimetallic interface, comprising the following steps:

[0035] Step 1: Electrochemical deposition of FeCoNiCr-M high entropy alloy coating;

[0036] Based on the redox characteristics of electrochemical technology and the first principles, Cu, Mn and Zn, which are close to the standard electrode potential of the four elements FeCoNiCr, are selected as the fifth principal element. With the help of the CASTEP module in the MaterialsStudio software, through geometric optimization simulation, the lattice parameters, mechanical properties (elastic constants, Poisson's ratio), thermodynamic parameters (system formation enthalpy and free energy) and physical properties (conductivity) of different FeCoNiCr-M high entropy alloys are clarified, the M component is optimized, and the influence of the salt solution concentration ratio of the five principal cations, the solution pH value and the type of additive solution parameters on the solid solution phase composition, element distribution, coating thickness and deposition rate of the high entropy alloy coating is systematically studied. Then, the single-factor experimental method is used to adjust the electrochemical process parameters of current density, solution temperature, deposition time and plating solution stirring frequency to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy.

[0037] XRD, SEM, TEM and EDS were used to characterize the phase structure and microstructure of the high entropy alloy coating, and thermodynamic calculations were used to clarify the solid solution phase formation mechanism of the high entropy alloy coating. The nano-hardness and elastic modulus of the coating were detected by a nano-indenter, and the bonding strength between the high entropy alloy coating and the steel substrate was obtained by a scratch tester. Combined with the analysis of microstructure and basic mechanical properties, the influence of solution parameters and electrochemical process parameters on the performance of the high entropy alloy coating were explored, revealing the corresponding relationship between the type / content of the main element, process parameters and the organizational properties of the high entropy alloy coating.

[0038] Step 2: Laser controllable construction of micro-textured high entropy alloy coating;

[0039] The texture pattern configuration that is conducive to improving the interface bonding strength (such as spiral, pit shape, etc.) is selected, and the micro-texture is constructed on the surface of the high-entropy alloy coating with excellent comprehensive performance by using femtosecond laser technology. By adjusting the texture pattern parameters (such as geometry, texture size, texture spacing, etc.) and laser process parameters (laser power, scanning speed, number of scans, etc.), the influence of pattern parameters and laser process parameters on the phase structure and basic properties of the high-entropy alloy coating is studied, and the filling law and spreading behavior of aluminum melt droplets on different texture surfaces are explored to provide suitable texture morphology for subsequent liquid-solid forming technology;

[0040] The three-dimensional morphology and two-dimensional profile curve of the texture pattern are obtained by laser 3D microscope to understand the variation law of the surface roughness of the micro-textured high-entropy alloy coating; SEM, XRD, EDS, XPS are used to detect the micro-morphology, element valence state and stress state of the micro-textured high-entropy alloy, revealing the burning behavior of the surface elements of the micro-textured high-entropy alloy and the stress distribution characteristics of the texture boundary; Through the solder wettability test, the influence of texture parameters on the high-temperature wetting performance of the aluminum alloy molten droplets used in Al / Fe bimetallic is clarified, and the laser process parameters are optimized in combination with SEM analysis feedback;

[0041] Step 3: Liquid-solid forming process optimization and microstructure and performance characterization of Al / HEA / Fe composites;

[0042] Based on the aforementioned process optimization parameters, a micro-textured high-entropy alloy coating was constructed on the surface of the steel substrate, and the whole was used as an embedded casting for liquid-solid forming research to explore the antioxidant ability of the micro-textured high-entropy alloy coating under different preheating conditions such as substrate surface state, preheating temperature, and preheating time; then the influence of different casting conditions such as aluminum liquid casting temperature, casting insulation time, and mold type on the composite interface reaction phase composition, element distribution state, reaction layer width change, and defect form was studied, and combined with kinetic analysis, the interface bonding characteristics and interface organization evolution of Al / HEA / Fe composites were revealed, and the reasons for the inhibition of aluminum-iron hard and brittle phases at the composite interface were clarified;

[0043] The phase composition / structure, element distribution, microstructure, grain size and orientation distribution interface characteristics of the interface reaction layer of the Al / HEA / Fe composite material were analyzed by SEM, EPMA, TEM, EDS and EBSD. The surface residual stress of the composite material was measured by X-ray diffraction. The residual stress at the interface was detected by nanoindentation. The hardness distribution of the composite material along the interface was analyzed by nanoindenter. The interface bonding strength of the composite material before and after the addition of high entropy alloy intermediate layer and before and after laser processing was tested and compared by universal testing machine. Combined with fracture morphology analysis, the interface strengthening mechanism of micro-textured high entropy alloy intermediate layer assisted liquid-solid forming of Al / Fe bimetal was elucidated.

[0044] Electrochemical deposition mechanism of FeCoNiCr-M series five-element high entropy alloy coating: Taking the four-element FeCoNiCr high entropy alloy as the basic research system, the electrochemical deposition mechanism of FeCoNiCr-M high entropy alloy coating is studied by adding alloying elements (such as Cu, Mn, Zn, etc.), adjusting the content of main elements and controlling process parameters:

[0045] Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of FeCoNiCr-M high entropy alloys are simulated and predicted, and the types of M principal elements in the FeCoNiCr-M system are optimized to provide theoretical guidance for the principal element design of electrochemically deposited FeCoNiCr-M high entropy alloy coatings.

[0046] The influence of solution parameters and electrochemical process parameters on the microstructure and properties of high-entropy alloy coatings is systematically investigated. Combined with thermodynamic calculations, the electrochemical deposition mechanism of the solid solution phase in the high-entropy alloy coating is clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties is established.

[0047] Laser controllable construction mechanism of microtexture on the surface of high entropy alloy coating:

[0048] Taking steel parts deposited with high-entropy alloy coatings with good comprehensive performance as processing objects, femtosecond laser technology is used to carry out research on the surface micro-texturing design and laser-controlled construction mechanism of high-entropy alloy coatings;

[0049] Systematically investigate the influence of laser process parameters on the microstructure and properties of high entropy alloy coatings, clarify the transformation behavior of the surface phase structure of high entropy alloys after laser irradiation; analyze the stress distribution characteristics, element burning behavior, and defect types of the surface of high entropy alloys, and reveal the laser action mechanism of the surface of high entropy alloy coatings;

[0050] Combined with high-temperature wetting performance tests, the filling state and spreading behavior of molten aluminum on the surface of micro-textured high-entropy alloy coatings are investigated, the influence of texture pattern parameters on the wetting performance of molten aluminum droplets is explored, and feedback is used to optimize the texture pattern parameters and laser process parameters.

[0051] Interface microstructure evolution and strengthening mechanism of liquid-solid formed Al / HEA / Fe composites:

[0052] Steel parts with micro-textured high entropy alloy coatings were used as embedded castings, and Al / HEA / Fe composites were prepared by liquid-solid forming technology. The evolution law of the interface structure and the strengthening mechanism of the composites were studied by optimizing the liquid-solid forming process.

[0053] Study the effects of liquid-solid forming process parameters on the element diffusion behavior / distribution characteristics, dissolution rate and reaction phase composition of high entropy alloy coatings, and clarify the interface bonding characteristics and organizational structure evolution of composite materials after the introduction of micro-textured high entropy alloy intermediate layers;

[0054] Through the microscopic characterization and bonding strength test of the composite material interface, assisted dynamic calculation, the composition / width changes, phase structure transformation and microtexture dissolution behavior of the composite material interface reaction layer are analyzed, revealing the interface regulation principle and interface strengthening mechanism of the composite material containing a microtextured high entropy alloy intermediate layer.

[0055] In summary, in response to the demand for high interface bonding strength of Al / Fe bimetallic, it is planned to use electrochemical and femtosecond laser composite technology to prepare micro-textured high entropy alloy coating, which will be used as an intermediate layer between the solid steel substrate and the liquid aluminum alloy melt, and the "Al / HEA / Fe composite material" will be obtained through liquid-solid forming technology. Based on thermal and kinetic calculations and experimental data analysis, through the optimization of high entropy alloy component / content, coating surface structure design and process parameter regulation, the formation mechanism of solid solution phase of high entropy alloy coating, the evolution law of composite material interface organization and interface strengthening mechanism are studied. Based on the cross-integration of multidisciplinary knowledge such as materials science, physical chemistry and computational materials science, an Al / HEA / Fe composite material with high interface bonding strength is developed by combining theoretical calculations with experimental analysis.

[0056] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for studying the effect of the intermediate layer on the assembly and performance of the bimetallic interface, characterized in that The following steps are involved: Step 1: electrochemical deposition of FeCoNiCr-M high entropy alloy coating; Based on the redox characteristics of electrochemical technology and the first principles, Cu, Mn and Zn, which are close to the standard electrode potential of the four elements FeCoNiCr, are selected as the fifth principal element. With the help of the CASTEP module in Materials Studio software, the lattice parameters, mechanical properties, thermodynamic parameters and physical properties of different FeCoNiCr-M high entropy alloys are clarified through geometric optimization simulation, and the M component is optimized. The influence of the salt solution concentration ratio of the five principal cations, the solution pH value and the type of additive solution parameters on the solid solution phase composition, element distribution, coating thickness and deposition rate of the high entropy alloy coating is systematically studied. Then, the single-factor experimental method is used to adjust the electrochemical process parameters of current density, solution temperature, deposition time and plating solution stirring frequency to achieve the controllable preparation of the solid solution phase structure of the high entropy alloy. XRD, SEM, TEM and EDS were used to characterize the phase structure and microstructure of the high entropy alloy coating, and thermodynamic calculations were used to clarify the solid solution phase formation mechanism of the high entropy alloy coating. A nanoindenter was used to detect the nanohardness and elastic modulus of the coating, and a scratch tester was used to obtain the bonding strength between the high entropy alloy coating and the steel substrate. Combined with the analysis of the microstructure and basic mechanical properties, the influence of solution parameters and electrochemical process parameters on the performance of the high entropy alloy coating were explored, revealing the corresponding relationship between the type / content of the main element, the process parameters and the organizational properties of the high entropy alloy coating. Step 2: Laser controllable construction of micro-textured high-entropy alloy coating; Optimize the texture pattern configuration that is conducive to improving the interface bonding strength, use femtosecond laser technology to construct micro-texture on the surface of high-entropy alloy coatings with excellent comprehensive performance, and study the influence of pattern parameters and laser process parameters on the phase structure and basic properties of high-entropy alloy coatings by adjusting texture pattern parameters and laser process parameters. Explore the filling law and spreading behavior of aluminum melt droplets on different texture surfaces to provide suitable texture morphology for subsequent liquid-solid forming technology; A laser 3D microscope is used to obtain the three-dimensional morphology and two-dimensional profile curve of the texture pattern to understand the variation law of the surface roughness of the micro-textured high-entropy alloy coating; SEM, XRD, EDS, and XPS are used to detect the microscopic morphology, element valence state, and stress state of the micro-textured high-entropy alloy to reveal the burning behavior of the surface elements of the micro-textured high-entropy alloy and the stress distribution characteristics of the texture boundary; through the solder wettability test, the influence of texture parameters on the high-temperature wetting performance of the aluminum alloy molten droplets used in the Al / Fe bimetallic is clarified, and the laser process parameters are optimized in combination with SEM analysis feedback; Step 3: Liquid-solid forming process optimization and microstructure and performance characterization of Al / HEA / Fe composites; Based on the aforementioned process optimization parameters, a micro-textured high-entropy alloy coating was constructed on the surface of the steel substrate, and the whole was used as an embedded casting for liquid-solid forming research to explore the antioxidant ability of the micro-textured high-entropy alloy coating under different preheating conditions such as substrate surface state, preheating temperature, and preheating time; then the influence of different casting conditions such as aluminum liquid casting temperature, casting insulation time, and mold type on the composite interface reaction phase composition, element distribution state, reaction layer width change, and defect form was studied, and combined with kinetic analysis, the interface bonding characteristics and interface organization evolution of Al / HEA / Fe composites were revealed, and the reasons for the inhibition of aluminum-iron hard and brittle phases at the composite interface were clarified; SEM, EPMA, TEM, EDS and EBSD were used to analyze the phase composition / structure, element distribution, organizational morphology, grain size and orientation distribution interface characteristics of the interface reaction layer of the Al / HEA / Fe composite material. The surface residual stress of the composite material was measured by X-ray diffraction. The residual stress at the interface was detected by nanoindentation. The hardness distribution of the composite material along the interface was analyzed by nanoindenter. The interface bonding strength of the composite material before and after the addition of the high entropy alloy intermediate layer and before and after laser processing was tested and compared by a universal testing machine. Combined with the fracture morphology analysis, the interface strengthening mechanism of the micro-textured high entropy alloy intermediate layer assisted liquid-solid forming of Al / Fe bimetal was elucidated.

2. The method for studying the effect of the intermediate layer on the assembly and performance of the bimetallic interface according to claim 1, characterized in that: Electrochemical deposition mechanism of FeCoNiCr-M series five-element high entropy alloy coating: Taking the four-element FeCoNiCr high entropy alloy as the basic research system, the electrochemical deposition mechanism of FeCoNiCr-M high entropy alloy coating is studied by adding alloying elements, adjusting the content of main elements and controlling process parameters: Based on the first principles, the crystallographic parameters, thermodynamic properties and physical properties of FeCoNiCr-M high entropy alloys are simulated and predicted, and the types of M principal elements in the FeCoNiCr-M system are optimized to provide theoretical guidance for the principal element design of electrochemically deposited FeCoNiCr-M high entropy alloy coatings. The influence of solution parameters and electrochemical process parameters on the microstructure and properties of high-entropy alloy coatings was systematically investigated. Combined with thermodynamic calculations, the electrochemical deposition mechanism of the solid solution phase in the high-entropy alloy coating was clarified, and the corresponding relationship between the main element type / element content, process parameters and coating microstructure and properties was established.

3. The method for studying the effect of the intermediate layer on the assembly and performance of the bimetallic interface according to claim 1, characterized in that: Laser controllable construction mechanism of microtexture on the surface of high entropy alloy coating: Taking steel parts deposited with high-entropy alloy coatings with good comprehensive performance as processing objects, femtosecond laser technology is used to carry out the design of surface micro-texturing of high-entropy alloy coatings and the research on the mechanism of laser-controlled construction; Systematically investigate the influence of laser process parameters on the microstructure and properties of high entropy alloy coatings, and clarify the transformation behavior of the surface phase structure of high entropy alloys after laser irradiation; Analyze the stress distribution characteristics, element burning behavior, and defect types of the high entropy alloy surface to reveal the laser action mechanism on the surface of the high entropy alloy coating; Combined with high-temperature wetting performance tests, the filling state and spreading behavior of molten aluminum on the surface of micro-textured high-entropy alloy coatings are investigated, the influence of texture pattern parameters on the wetting performance of molten aluminum droplets is explored, and feedback is used to optimize the texture pattern parameters and laser process parameters.

4. The method for studying the effect of the intermediate layer on the assembly and performance of the bimetallic interface according to claim 1, characterized in that: Interface microstructure evolution and strengthening mechanism of liquid-solid formed Al / HEA / Fe composites: Steel parts with micro-textured high entropy alloy coatings were used as embedded castings, and Al / HEA / Fe composites were prepared by liquid-solid forming technology. The evolution law of the interface structure and the strengthening mechanism of the composites were studied by optimizing the liquid-solid forming process. Study the effects of liquid-solid forming process parameters on the element diffusion behavior / distribution characteristics, dissolution rate and reaction phase composition of high entropy alloy coatings, and clarify the interface bonding characteristics and organizational structure evolution of composite materials after the introduction of micro-textured high entropy alloy intermediate layer; Through the microscopic characterization and bonding strength test of the composite material interface, assisted by kinetic calculations, the composition / width changes, phase structure transformation and microtexture dissolution behavior of the composite material interface reaction layer are analyzed, revealing the interface regulation principle and interface strengthening mechanism of composite materials containing micro-textured high-entropy alloy intermediate layers.

Citation Information

Cited By

  • Wear-resistant alloy casting part for electric machinery and production process of wear-resistant alloy casting part

    CN120158690A

  • Method for preparing aluminum-iron composite material based on microstructure and aluminum-iron composite material

    CN120839035A